STRATEGI PROMOSI PULAU MOMONGAN PADA ERA NEW NORMAL DI KABUPATEN CILACAP - Esih Jayanti; Rustina Dewi Werdiasih (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
Momongan is one of the potential for marine tourism in Cilacap Regency which has the potential to developed. Momongan Island is located in Jetis Village, in the karst mountains and in the middle of the Bodo Ijo river which must be reached by boat from the Jetis Fish Auction Place. There ere a lot of people inside and outside of the Cilacap Regency do not know about the destinations of Momongan Island, so the promotion of Momongan Island is very necessary. The media used to promotions in the new normal era as today is sosial media which is low-budget high-impact. The purpose of this study is to develop Momongan Island through an effective promotion strategy as a leading tourist destination in Cilacap Regency based on competitive advantage in the New Normal. This study used a accidental sampling technique with 195 interviewed respondents stated that Momongan Island needs more promotion. Next step, the quesionnaire data from 103 sample respondent who use instagram was processed using Regression analysis by testing dependent and independent variable. The result of the analysis show that sosial media Instagram is a suitable tool as a promotional media for Momongan Island.